2018
DOI: 10.1097/qad.0000000000001824
|View full text |Cite
|
Sign up to set email alerts
|

Monotypic low-level HIV viremias during antiretroviral therapy are associated with disproportionate production of X4 virions and systemic immune activation

Abstract: Objective:During effective antiretroviral therapy (ART), low-level plasma viremias (LLV) (HIV RNA >30–1000 copies/ml) can be detected intermittently. We hypothesized that systemic inflammation is associated with LLV either as the cause or result of the production of virions from clonally expanded cells.Methods:Prospective cohort study of HIV-infected ART-naive Peruvians enrolled prior to ART and followed for 2 years. Plasma HIV RNA and peripheral blood mononuclear cell (PBMC) HIV DNA concentrations were quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 74 publications
0
13
1
Order By: Relevance
“…While previous studies of low-level intermittent viremias (plasma HIV RNA 50-400 c/mL) [29,50] occasionally detected evidence of HIV replication, genetic divergence of our participants' sequences was detected only after frequent or prolonged ART-interruptions. No significant increase in viral divergence was observed among plasma sequences imputed to use the CCR5 co-receptor during the first period of ART suppression in all 3 participants, suggesting the lack of ongoing viral replication during effective ART.…”
Section: Plos Pathogenscontrasting
confidence: 79%
See 1 more Smart Citation
“…While previous studies of low-level intermittent viremias (plasma HIV RNA 50-400 c/mL) [29,50] occasionally detected evidence of HIV replication, genetic divergence of our participants' sequences was detected only after frequent or prolonged ART-interruptions. No significant increase in viral divergence was observed among plasma sequences imputed to use the CCR5 co-receptor during the first period of ART suppression in all 3 participants, suggesting the lack of ongoing viral replication during effective ART.…”
Section: Plos Pathogenscontrasting
confidence: 79%
“…However, the absence of detectable divergence despite viremia during ART-interruptions of Participants 1 and 2 demonstrates that divergence is insensitive to short periods of low-level virus replication, and emphasizes that a lack of divergence does not provide certainty that HIV replication did not contribute to RV. The detection of multiple RV sequences predicted to use the X4 co-receptor that cluster closely in the phylogenetic analyses of Participant 1, and in multiple individuals in previous studies of low-level viremias [29,50] leads us to speculate that X4 tropism is selected for persistence and/or replication during ART-suppression.…”
Section: Plos Pathogensmentioning
confidence: 69%
“…Low-level viremia during ART can be due to separate mechanisms: release of viral particles from latently infected cells and active replication [ 27 ]. Interestingly, different profiles of inflammatory cytokines have been associated with 2 distinct HIV env sequence patterns, monotypic and diverse LLV [ 28 ]. Biological pathways might therefore explain an association between LLV and adverse clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Variants predicted to use the X4 receptor were found in the plasma viral rebound in a minority of participants (3/7, 43%). Previously we 47 and others 44 found that X4 variants are prevalent in low-level viremias of otherwise ART-suppressed participants. The presence of X4 variants in the plasma rebound might reflect the late disease stage of participants [48][49][50] or it could indicate a previously unappreciated latent reservoir in naive T cells or those of the myeloid lineage that express high concentrations of the CXCR4 receptor.…”
Section: Discussionmentioning
confidence: 79%